2004
DOI: 10.1158/1078-0432.ccr-1122-3
|View full text |Cite
|
Sign up to set email alerts
|

Epstein-Barr Virus-Positive Gastric Carcinoma Has a Distinct Protein Expression Profile in Comparison with Epstein-Barr Virus-Negative Carcinoma

Abstract: Purpose: EBV has been detected in 2-16% of gastric carcinomas. However, there is little information available about the gene expression profile of EBV-positive gastric carcinomas.Experimental Design: EBV infection was examined using EBV-encoded small RNAs (EBERs) in situ hybridization, and 63 (5.6%) of 1127 consecutive gastric carcinomas were found to be EBV-positive. The expressions of 27 tumorassociated proteins were evaluated immunohistochemically in 63 EBV-positive gastric carcinomas and 287 EBV-negative c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
72
4
7

Year Published

2005
2005
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 113 publications
(88 citation statements)
references
References 20 publications
5
72
4
7
Order By: Relevance
“…The prevalence of EBV infection in our gastric AC cases corresponds well with the findings of others, where frequencies between 5% and 14% have been reported. 10,11 On the other hand, we cannot substantiate the results of Corvalan et al,…”
contrasting
confidence: 81%
“…The prevalence of EBV infection in our gastric AC cases corresponds well with the findings of others, where frequencies between 5% and 14% have been reported. 10,11 On the other hand, we cannot substantiate the results of Corvalan et al,…”
contrasting
confidence: 81%
“…Although previous studies of EBV DNA in gastric tumour tissue and survival have produced inconsistent results (Chang et al, 2001;Lee et al, 2004), some have found improved survival associated with EBV, at least in subgroups (Koriyama et al, 2002;Lee et al, 2004;van Beek et al, 2004). Our association between high EBNA titres and improved survival was also limited to a subgroup, cardia cancers, although this finding may be due to chance.…”
Section: Discussionmentioning
confidence: 56%
“…In cases where more than 10% of tumor cells are immunoreactive, immunostaining is regarded as positive 27,28 or high labeling index for Ki-67. 29 MUC1, MUC2, MUC5AC, and MUC6 protein expression status is positive when more than 20% of the tumor cells display immunoexpression in the cytoplasm.…”
Section: Immunohistochemistrymentioning
confidence: 99%